Uncovering the Anti-bacterial Potential of Wildly Growing Chamaedorea seifrizii Fruits Targeting Peptidoglycan Editing Factor Proteins: Chemical Profiling, In-silico Analysis and Wet Lab Validation - Sharma, Arun Dev; Kaur, Inderjeet; Chauhan, Amrita (Sciences of Phytochemistry, 2026)
Chamaedorea seifrizii is an ornamental plant with limited documented pharmacological properties. Peptidoglycan editing factor (PdeF), a bacterial cytoplasmic amidase, plays a critical role in peptidoglycan biosynthesis of the bacterial cell wall, making it a promising antibacterial target. This study investigated the chemical profiling and in-silico analysis of phytocomponents derived from methanol fruit extracts (CFME) of wild-growing Chamaedorea seifrizii targeting PdeF proteins, followed by in vitro antibacterial validation. The chemical profile of CFME was examined using gas chromatography with flame ionization detection (GC-FID). Molecular simulation studies were performed using docking tool Cb-dock2 against bacterial PdeF. In vitro activity was validated against Gram-negative strains, Pseudomonas aeruginosa (MTCC 424) and Escherichia coli (MTCC 40), and Gram-positive strains, Staphylococcus aureus (MTCC 3160) and Bacillus subtilis (MTCC 121). GC-FID analysis revealed 13 peaks, with osthole as the most abundant phytocompound at 27.49%. Docking of osthole against PdeF showed binding energy of -6.8 kcal/mol, indicating moderate affinity, with the complex stabilized through hydrogen bonding, alkyl and pi-alkyl interactions. In vitro experiments confirmed effective bacterial growth inhibition, with zones of inhibition ranging from 2 mm to 17 mm, compared to reference antibiotic yielding nil to 15 mm. To the best of our knowledge, this is the first report on bioactive components from Chamaedorea seifrizii fruit methanol extracts with antibacterial activity targeting PdeF through a combined in vitro and in-silico approach. These findings highlight the potential of Chamaedorea seifrizii as an antibacterial agent, underscoring the need for further compound-level characterization and safety assessment for applications in pharmaceutical industries.